2007
DOI: 10.1109/iembs.2007.4353071
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Skin Repigmentation Progression

Abstract: In this paper, we describe an image processing scheme to analyze and determine areas of skin that have undergone repigmentation in particular, during the treatment of vitiligo. In vitiligo cases, areas of skin become pale or white due to the lack of skin pigment called melanin. Vitiligo treatment causes skin repigmentation resulting in a normal skin color. However, it is difficult to determine and quantify the amount of repigmentation visually during treatment because the repigmentation progress is slow and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…12 Recently, Nugroho et al introduced an image analysis method that quantify vitiligo lesion in terms of image segmentation. 20 However, vitiligo can not be quantified only with area information because the cycling of 6-BH 4 is impaired in the vitiligo, leading to time-dependent accumulation of 7-BH 4 in the vitiligo, so that the concentrations of 6-and 7-biopterins are increased as a result of photo-oxidation process; that is, during improvement, the vitiligo area can be consistent while the concentration of the biopterins, which are the prominent endogenous fluorophores in vitiligo lesion, can be decreased. 15,[17][18] To verify the fact, we evaluated vitiligo lesion with UV-A radiation and demonstrated that quantitative and clinical meaningful analysis can be achieved with 2-D profiling of the biopterins distribution ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…12 Recently, Nugroho et al introduced an image analysis method that quantify vitiligo lesion in terms of image segmentation. 20 However, vitiligo can not be quantified only with area information because the cycling of 6-BH 4 is impaired in the vitiligo, leading to time-dependent accumulation of 7-BH 4 in the vitiligo, so that the concentrations of 6-and 7-biopterins are increased as a result of photo-oxidation process; that is, during improvement, the vitiligo area can be consistent while the concentration of the biopterins, which are the prominent endogenous fluorophores in vitiligo lesion, can be decreased. 15,[17][18] To verify the fact, we evaluated vitiligo lesion with UV-A radiation and demonstrated that quantitative and clinical meaningful analysis can be achieved with 2-D profiling of the biopterins distribution ( Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Nugroho et al 36 proposed an image analysis method that measured the area of vitiligo lesions based on image segmentation, in order to evaluate the repigmentation progression. However, vitiligo cannot be quantified only by considering its area because the cycling of 6-BH 4 can be impaired in vitiligo lesions, leading to time-dependent accumulation of 7-BH 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Using PCA for extracting blood and melanin values has been proposed [26], showing that skin color in digital RGB images can be described by the first two principal components. PCA and independent component analysis (ICA) have also been applied to RGB imaging data for extraction of blood and melanin values in vitiligo lesions to qualitatively evaluate the skin re-pigmentation progression [27], [28]. Our group has shown previously [29] that PCA applied to multispectral images from the skin in the wavelength range between 750 nm and 850 nm can be used for mapping the blood volume and blood oxygenation, where the first eigenvector (first principal component) describes the blood volume and the second eigenvector corresponds to the blood oxygenation.…”
Section: Introductionmentioning
confidence: 99%